2013
DOI: 10.1590/s0103-84782013005000009
|View full text |Cite
|
Sign up to set email alerts
|

Cytology profile and age influence in the equine bronchoalveolar lavage in healthy and asymptomatic inflammatory airway disease

Abstract: Perfil citológico e influência da idade no lavado broncoalveolar de equinos sadios e com doença inflamatória de vias aéreas assintomática were, respectively: 56.9% and 48.0% macrophages, 37.2% and 40.0% lymphocytes, 3.3% and 7.1% neutrophils, 1.7% and 1.4% mast cells, 0.3% and 0.7% eosinophils; 0,5% and 0.4% epithelial cells. When Palavras-chave: equino, doença inflamatória das vias aéreas, citologia broncoalveolar. ABSTRACT Pulmonary inflammatory diseases have been observed in equine since their domes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
2
5
2
Order By: Relevance
“…The occurrence of IAD in this study was similar to the reported occurrence in horses in military use [ 30 ] and lower than that observed in racehorses [ 9 , 36 ]. Two factors that must be considered are the time period in which the endoscopic examination occurred (at rest or post exercise) and the subjectivity of the observer.…”
Section: Discussionsupporting
confidence: 87%
“…The occurrence of IAD in this study was similar to the reported occurrence in horses in military use [ 30 ] and lower than that observed in racehorses [ 9 , 36 ]. Two factors that must be considered are the time period in which the endoscopic examination occurred (at rest or post exercise) and the subjectivity of the observer.…”
Section: Discussionsupporting
confidence: 87%
“…In our population, the TNNC of the BALF was similar to what has already been described in healthy horses (Pacheco et al, 2014;Mendoza et al, 2018) and donkeys (Campi et al, 2008;Shawaf, 2019). In agreement with what has already been described in horses, no differences in the differential count were observed according to the age and sex of the subjects (Porto Sad et al, 2013;Pacheco et al, 2014). The reason for the difference in TNNC between males and females is unclear, and it is possibly a type II error caused due to the small sample size.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Sad et al (2013), endoscopic examination was used to identify horses with asymptomatic airway inflammatory disease in a population of horses considered clinically healthy. Thirty-two adult horses of mixed breeds underwent endoscopic examination, and 53.12% of them presented tracheal mucus scores of II to IV, which is considered a sign of asymptomatic mild/ moderate asthma.…”
Section: Endoscopic Findingsmentioning
confidence: 99%